2009
DOI: 10.1007/s00701-009-0218-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the long-term results of anterior transposition of the ulnar nerve or simple decompression in the treatment of cubital tunnel syndrome—a prospective study

Abstract: These long-term results show that both surgical techniques have a good outcome. Thus, the less invasive simple decompression should be preferred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 29 publications
0
39
0
4
Order By: Relevance
“…A recent article reported that the patients treated with AT had inferior outcome when compared with patients treated with SD and partial epicondylectomy [11]. Meanwhile, another article reported that although both SD and AT had a good outcome, the SD should be preferred due to less invasion [12]. However, two previous meta-analyses have suggested that there was no statistically significant difference between SD and AT [13,14].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…A recent article reported that the patients treated with AT had inferior outcome when compared with patients treated with SD and partial epicondylectomy [11]. Meanwhile, another article reported that although both SD and AT had a good outcome, the SD should be preferred due to less invasion [12]. However, two previous meta-analyses have suggested that there was no statistically significant difference between SD and AT [13,14].…”
Section: Introductionmentioning
confidence: 90%
“…The average follow-up duration ranged from 12 to 76 months. Four out of 13 studies [6,12,21,26] were the high quality studies with the score over 3.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…We asked patients about their current complaints in the 3 clinical modalities, and we asked them how they felt about their current symptoms overall compared with their symptoms before the revision surgery, similar to several other studies but more elaborate. 2,12,18 Satisfaction was graded on a 6-point scale: 1, complete resolution of symptoms; 2, moderate resolution of symptoms; 3, no change; 4, slight increase in symptoms; 5, moderate increase in symptoms; 6, severe increase in symptoms. The patients also indicated if, in hindsight, they would opt for revision surgery again, considering their current outcome.…”
Section: Data Collectionmentioning
confidence: 99%